306 Open Source Informatics to Enrich Value of Laboratory Data, Hepatitis C Reporting Example. (11th January 2018) - Barasch, Samuel; Adem, Patricia; Fallon, John
Abstract: Introduction: In order to ensure compliance with a New York State Department of Health mandate, the laboratory was asked to provide a weekly report of patients with a date of birth (DOB) between January 1, 1945, and December 31, 1965, who had positive or equivocal hepatitis C (HepC) serologic testing. The laboratory sought to enrich the reports provided by the laboratory information system (LIS) vendor, as these required manual manipulation in order to identify the target demographic with first-time positive or equivocal results only. Methods: Weekly reports generated by the LIS included all HepC serologic testing for patients in the target demographic. These reports were converted to tab delimited text files. The weekly report then has all "non-reactive" results removed. The processed HepC results were compared to a 10-year archive of HepC serologic data (archive constructed with Linux file management tools; approximately 2, 300 results). The PERL code, which compared the weekly report to the archive, matched patients based on medical record number and DOB. When a patient was matched, the date and number of the order associated with the prior positive result was inserted into the file. Finally, the weekly report with non-reactive results excluded was appended to the archive. Examples of file and text processing utilities in the Linux platform and PERL programming language will be discussed. Conclusion: The system adds value to vendor LIS reports by removing non-reactive results and stratifying patients into those with a prior positive test and those for whom the result represents a first positive test recorded in the LIS. The system does not provide confirmation or acknowledgement of the current or past positive results by the patient's clinical care team. The report highlights problems with test utilization. Though vendor licensing is not necessary for open source software, development and staff training time are system expenses.